Adsorption of Methylene Blue in Aqueous Solution Using Hydrogels Based on 2-Hydroxyethyl Methacrylate Copolymerized with Itaconic Acid or Acrylic Acid - Sanchez-Poblete, J; Oyarce-Riveros, E (Elsevier Ltd, 2020)
In this research, the adsorption of methylene blue (MB) dye in aqueous solution was studied using cross-linked copolymers based on 2-hydroxyethyl methacrylate (HEMA) copolymerized with itaconic acid (IA) and acrylic acid (AA). The structural composition of the copolymers was corroborated by means of Fourier transform infrared spectroscopy and the thermal stability was studied by thermogravimetry. The presence of irregular morphology with porous and rough areas was observed by scanning electron microscopy. Hydrogels were sensitive to pH changes, demonstrating greater hydration capacity at pH 9.0 for systems constituted by lower concentration of cross-linked agent. The adsorption capacity of MB showed values of 260 mg g−1 and 197 mg g−1 for P(HEMA-co-IA) and P(HEMA-co-AA) respectively. These results were obtained in MB solutions with an initial concentration of 1 g L-1, at pH 8.0 using 0.2 g of copolymer and 24 h of contact time. The adsorption-desorption of MB was governed by the variation of pH, and the reuse of copolymer adsorbents in three consecutive cycles was verified. In addition, the adsorption kinetics revealed that the equilibrium time reached in the adsorption process was 300 min, adjusting to the pseudo second order kinetic model. © 2020 Elsevier Ltd